THE LAW PROTECTION FOR OWNERS OF INTELLECTUAL PROPERTY RIGHTS TO IMAGE TAKEN FROM THE INTERNET FOR ECONOMIC BENEFITS - Iwan Purwanto; Anak Agung Ngurah Tini Rusmini Gorda (Jurnal Analisis Hukum, 2019)
This study examines the law protection for owners of intellectual property rights to images taken from the internet for economic benefit. Image is one of the copyrighted works protected by the Act, namely Law Number 28 of 2014 concerning Copyright. But in practice there are often violations of copyrighted works that are the property of a creator. The problem raised is how the legal protection for owners of intellectual property rights is if the image is taken for economic benefit and how sanctions are imposed on violating economic rights to images taken from the internet and the implementation of sanctions against violations of economic rights to images taken from the internet. The theory used in this study is the theory of legal protection and the theory of legal responsibility and the method of research used the statue of approach. The results showed that the protection given to image copyright can be done preventively, namely legal protection provided by the government in order to prevent violations by providing convenience and and given incentive for owner of Intellectual Property Rights when registering Copyright to the Directorate General of Intellectual Property Rights and repressive protection, namely legal protection granted the government with the aim of resolving disputes in the event of a violation by filing a lawsuit to the Commercial Court. The conclusion of this research is The implementation of sanctions against violations of economic rights to images can be subject to imprisonment and or criminal penalties as stipulated in Article 9 of the Copyright Act No. 28 of 2014 while the implementation of sanctions on copyright protection for images circulating on the internet is specifically regulated (lex specialists) in Article 48 of Law Number 19 Year 2016 concerning Information and Electronic Transactions. Keywords: The law protection, Intellectual Property Right for Image, Economic Benefits